Foot Length as a Predictor of Weight in Children up to Five Years - Shameem, Md; Banu, Nazneen Akhter; Bhuiyan, ANM Nurul Haque; Islam, Ariful (TAJ: Journal of Teachers Association, 2019)
Weight measurement is essential for the management of pediatric patients to calculate the dose of the drugs. But it is not possible to move the child to a weighing scale for determination of body weight when the child is in a critical condition. The purpose of this study was to check if foot length correlates with child’s body weight in our situation and to devise a formula for prediction of weight based on foot– length observed. This Cross-sectional study was carried out in the Department of Pediatrics, Sir Salimullah Medical College, Mitford hospital, Dhaka over a period of 12 months between January 2008 and December 2008. A total of 300 children, between 0 day to five years, meeting the predefined eligibility criteria were included in the study. Using the available data, simple linear regression analysis was performed between the dependent variable weight and independent variable foot length. The estimated linear regression line was: Predicted weight (kg) = a+ [b× foot length]. Data were analyzed using correlation coefficient (r) between foot length and children’s weight. In this study correlation between foot length and weight (r) was 0.92(P<0.001) indicating a perfect linear relationship between them. In the present study determination of correlation (r2) was 0.85 meaning that 85% of the variability in weight might be explained by variation in foot length. The estimated linear regression line was: Predicted weight (kg) = - 4.64 + [1.12 X foot length], where- 4.64 was the intercept and 1.12 was the slope of the regression line. Comparison between measured weight and predicted weight revealed that94% of variation between measured weight and predicted weight was within ±2kg. More than half of the cases (58.3%) the above-mentioned variations were within ±1kg. This study concluded, there was a strong correlation between foot length and weight in children up to five years. The body weight in children from 0 days up to the age of 5 years can be predicted from foot length. Prediction of weight simply by foot-length measurement could be a great help to the health care provider including doctors and health workers for drug dose calculation in critically ill children. TAJ 2018; 31(2): 39-44